Laser-Driven Rapid Synthesis of Metal-Organic Frameworks and Investigation of UV-NIR Optical Absorption, Luminescence, Photocatalytic Degradation, and Gas and Ion Adsorption Properties - Mutlu, Saliha; Ortac, Buelend; Ozbey, Dogukan Hazar; Durgun, Engin; Savaskan Yilmaz, Sevil; Arsu, Nergis (MDPI, 2024)
In this study, we designed a platform based on a laser-driven approach for fast, efficient, and controllable MOF synthesis. The laser irradiation method was performed for the first time to synthesize Zn-based MOFs in record production time (approximately one hour) compared to all known MOF production methods with comparable morphology. In addition to well-known structural properties, we revealed that the obtained ZnMOFs have a novel optical response, including photoluminescence behavior in the visible range with nanosecond relaxation time, which is also supported by first-principles calculations. Additionally, photocatalytic degradation of methylene blue with ZnMOF was achieved, degrading the 10 ppm methylene blue (MB) solution 83% during 1 min of irradiation time. The application of laser technology can inspire the development of a novel and competent platform for a fast MOF fabrication process and extend the possible applications of MOFs to miniaturized optoelectronic and photonic devices.
Keywords: metal-organic framework; laser method; photocatalytic activity; adsorption; INITIO MOLECULAR-DYNAMICS; METHYLENE-BLUE; ZN-MOF; FABRICATION; FILMS; GRAPHENE; Polymer Science